Arteriosclerosis in dialysis patients - Bommer, Jürgen; Strohbeck, E.; Görich, Johannes; Bahner, Malte Leonardo; Zuna, Ivan (Artificial organs, 1996)
Arteriosclerosis is a constant problem in long-term hemodialysis patients. Computer tomography of the abdominal aorta allows a well-defined and reproducible evaluation of aortosclerosis. In the cross-sectional study, aortosclerosis was significantly accelerated in 84 chronic hemodialysis patients and was comparable to the results found in 20-year older control patients without renal disease. The increase of aortosclerosis correlated significantly with age of the patient, smoking, and duration of dialysis therapy. Furthermore, increased VLDL cholesterol and decreased HDL cholesterol seem to enhance aortosclerosis in our dialysis patients. In the longitudinal study (two CT scans with a time interval of 87 ± 62.7 months) in 36 dialysis patients, progressed aortosclerosis correlated significantly with the long duration of hypertriglyceridemia, VLDL cholesterol, uric acid, and calcium phosphate products. Progression of aortosclerosis was reduced in parathyroidectomized patients. The study suggests that premature aortosclerosis is found in dialysis patients. In addition to the common risk factor of aortosclerosis, disturbed calcium phosphate and parathyroid hormone metabolism seem to enhance aortosclerosis in patients under maintenance hemodialysis.